The Effect of Discounts and Trust on Purchase Decisions in Live Steraming Sales og The Tiktokshop Application in Banda Aceh - Zenitha Maulida; Farah Ivana; Nurbismi; Indra Kesuma (Universitas Pelita Harapan, 2025)
Purchasing products online makes it easier to shop without wasting a lot of time and energy. One innovation in this industry is the live streaming feature offered by the TikTok application, namely Tiktokshop, which allows sellers to interact directly with buyers in real-time. This study aims to analyze the influence of discounts and trust on purchasing decisions during live streaming on the TikTok application in Banda Aceh. This study uses a quantitative approach. The data collection technique was carried out by distributing questionnaires to a sample of 200 respondents. The sampling method in this study used purposive sampling. The data analysis method used is multiple linear regression analysis. The results show that the variables of discounts and trust have a positive and significant effect on purchasing decisions during live streaming sales on the TikTok application in Banda Aceh.